2001
DOI: 10.1348/135910701169070
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous, elicited and cued causal attributions in the year following a first myocardial infarction

Abstract: Patients do provide causal attributions following an MI. While many are similar to causal factors identified by medicine, patients appear to place more emphasis on 'stress'. As predicted by attribution theory, attributions changed over time. The method of obtaining the attributions does not appear to affect the attributions made but greatly affects their number. While all the methods used have their place, the cued method with a list of possible attributions offers a rich return for effort expended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
4
12
0
Order By: Relevance
“…The overall ranking of causes in this study was comparable with several previous reports, with stress, smoking, and high blood pressure being the most frequently endorsed factors [5,6,9]. The proportion of patients endorsing these causes was higher than in some other studies.…”
Section: Discussionsupporting
confidence: 88%
“…The overall ranking of causes in this study was comparable with several previous reports, with stress, smoking, and high blood pressure being the most frequently endorsed factors [5,6,9]. The proportion of patients endorsing these causes was higher than in some other studies.…”
Section: Discussionsupporting
confidence: 88%
“…This is in keeping with a previous study, which examined different approaches to examining different methods of eliciting causal beliefs for MI (Gudmundsdottir et al, 2001), and with a systematic review of the literature as a whole (French et al, 2001). However, although there are similarities in the patterns of responses of whole samples, for these measures to demonstrate reliability, and thus allow validity, it is necessary for individuals to demonstrate consistency in patterns How valid are measures of beliefs about the causes of illness?…”
Section: Causal Beliefs Elicited By Open-ended and Structured Questiosupporting
confidence: 77%
“…A direct comparison of these two methods with 100 MI patients showed that the use of structured questionnaires resulted in more causes being endorsed (Gudmundsdottir et al, 2001). Despite this, the ordering of attributions in terms of which were most prevalent, did not differ between the two methods.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The relative paucity of attributional statements is similar to that seen in a study of spontaneous causal attributions made by patients following a myocardial infarction (23). People usually engage in causal search when they encounter unexpected, negative events (10).…”
Section: Research Question 4: Attributions and Psychological Adjustmentsupporting
confidence: 53%